Answer:
–3 and –3
Explanation:
x² + 6x = – 9
Rearrange
x² + 6x + 9 = 0
Multiply the first term i.e x² and last term i.e 9 together. The result is 9x².
Next, we shall find two factors of 9x² such that when we add them together, the result will be the same as the 2nd term i.e 6x in the expression above.
The factors are 3x and 3x.
Next, we shall replace 6x with 3x and 3x in the equation above as shown below:
x² + 6x + 9 = 0
x² + 3x + 3x + 9 =0
Factorise
x(x + 3) + 3(x + 3) = 0
(x + 3)(x +3) = 0
x + 3 = 0 or x + 3 =
x = – 3 or x = – 3
Therefore, the solutions are –3 and –3